2020
DOI: 10.1002/jsfa.10179
|View full text |Cite
|
Sign up to set email alerts
|

Residue dissipation and dietary exposure risk assessment of methoxyfenozide in cauliflower and tea via modified QuEChERS using UPLC/MS/MS

Abstract: BACKGROUND Methoxyfenozide possesses efficacy against a variety of lepidopteron pests, including the major pests in cauliflower and tea, so it is of great importance to generalize the practical use of methoxyfenozide in the field. RESULTS An efficient method was developed and validated in both vegetable matrix and extract‐rich matrix (cauliflower and tea) using modified QuEChERS combined with UPLC/MS/MS analysis. The recoveries in cauliflower, made tea and tea shoots ranged from 94.5 to 108.0%, from 85.0 to 91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The half-lives in the other three provinces (Beijing, Anhui, and Shandong) were quite close, which were 3.0, 4.0, 5.1 days for methoxyfenozide, and were 1.3, 2.5, and 2.3 days for metaflumizone. The results were close to the dissipation rates of methoxyfenozide in cauliflower [16], of which the half-lives were 2.5-3.5 days.…”
Section: Dissipation Of Methoxyfenozide and Metaflumizone In Chinese Broccoli Under Field Conditionssupporting
confidence: 78%
See 1 more Smart Citation
“…The half-lives in the other three provinces (Beijing, Anhui, and Shandong) were quite close, which were 3.0, 4.0, 5.1 days for methoxyfenozide, and were 1.3, 2.5, and 2.3 days for metaflumizone. The results were close to the dissipation rates of methoxyfenozide in cauliflower [16], of which the half-lives were 2.5-3.5 days.…”
Section: Dissipation Of Methoxyfenozide and Metaflumizone In Chinese Broccoli Under Field Conditionssupporting
confidence: 78%
“…A few reports have been published about residue analysis of methoxyfenozide and metaflumizone in vegetables. Sun et al [16] studied the residue dissipation of methoxyfenozide in cauliflower and tea by a modified QuEChERS sample preparation method combined with UHPLC-MS/MS, and they found that methoxyfenozide dissipated rapidly in cauliflower with a half-life of 2.5-3.5 days. Dong et al [17] developed a method for determination of metaflumizone residues in cabbage and soil by UHPLC-MS/MS using primary secondary amine (PSA) sorbent for cleanup.…”
Section: Introductionmentioning
confidence: 99%
“…For the safe application of propiconazole, dietary exposure calculation and risk assessment were studied based on the risk quotient (RQ) method. RQ < 100% indicates that the human exposure concentration by consumption of pesticide‐containing food is lower than the predicted effect concentration, representing an acceptable risk to humans, whereas RQ > 100% indicates unacceptable adverse health effects on humans 19–21 …”
Section: Methodsmentioning
confidence: 99%
“…19 To the best of our knowledge, scarcely any studies about the simultaneous determination of tolfenpyrad, dinotefuran and its metabolites in tea have been reported to date. Furthermore, although research has been carried out on the dissipation of pesticides during tea planting, processing and brewing, 1,3,4,[20][21][22][23][24] scarcely any literature has reported in the residue behavior and brewing transfer of tolfenpyrad, dinotefuran and its metabolites in tea. Therefore, it is significant to establish a reliable method for the simultaneous determination of tolfenpyrad, dinotefuran and its metabolites in tea, and use this to investigate their behavior during tea growth and tea brewing.…”
Section: Introductionmentioning
confidence: 99%